A review of cassava semolina (gari and eba) end‐user preferences and implications for varietal trait evaluation - Awoyale, Wasiu; Oladeji, Emmanuel; Chijioke, Alamu Ugo; Tran, Thierry; Noel, Hubert; Tchuente, Takam; Ndjouenkeu, Robert; Kegah, Ngoualem; Maziya‐Dixon, Busie (Wiley, 2021)
The purpose of this review is to support breeders and food scientists by examining research carried out on end-user preferences for gari and its derived dough product, eba, in Africa. The review focused on gari regarding the physical and chemical composition of raw cassava roots, methods of storage, the composition of gari with or without enrichment, and the sensory evaluation of gari and eba. The primary sensory attributes identified to describe gari are colour, taste, texture, aroma and flavour. Texture attribute of importance is crispiness for uncooked gari, and hand feel before consumption for eba. There was a significant correlation between the sensory characteristics of gari and the starch and cyanogenic potential (CNP) contents of the raw roots. Hence, the correlation of the end-user preferences with the chemical composition of the cassava roots could be helpful to breeders in refining selection criteria and developing high-throughput screening methods.